Design and Analysis of Spaceborne Hyperspectral Imaging System for Coastal Studies - Wu, Yin; Wang, Yueming; Zhang, Dong (Remote sensing (Basel, Switzerland), 2025)
Hyperspectral payloads with high spatial and spectral resolution, combined with a wide field of view, are crucial for tackling the complexity of coastal and estuarine water ecosystems, enabling effective monitoring of water quality and ecological conditions. This study introduces a modular spectrometer design utilizing multiple sub-modules in an extended slit configuration. The system delivers a spectral resolution of 5 nm (400–1000 nm) and 10 nm (1000–2500 nm), a spatial resolution of 20 m, and a swath width of 80 km. Smile and keystone distortions are maintained below 1/5 of a pixel. Using Modran to simulate solar irradiance, the SNR of different targets under typical background conditions is calculated. Compared to conventional designs, the proposed modular approach provides compactness and high fidelity, effectively addressing size and optical aberration challenges. The simulation results confirm the system’s robustness, setting a benchmark for next-generation coast observation missions, particularly in coastal monitoring, underwater exploration, and dynamic environmental change tracking.